An International Initiative in Biotechnology: Priorities, Values, and Implementation of an A.I.D. Project - Cohen, Joel I. (Wiley, 1993)
Biotechnology is a recent addition to international crop improvement. for its contribution to be effective, it must be fully integrated with conventional agricultural research. Based on recommendations contained in a National Research Council (NRC) report, the Agency for International Development (A.I.D.), in collaboration with the International Agricultural Research Centers (lARCs) and National Agricultural Research Systems (NARS), prioritized biotechnology research relevant to agricultural problems of the developing world and identified those suitable for mutually beneficial research. A new plant biotechnology project was designed, awarded, and implemented to address these priorities while complementing other international programs. The Agricultural Biotechnology for Sustainable Productivity (ABSP) project supports separate public and commercially oriented research efforts by providing multiple routes for the development and release of germplasm. These efforts are implemented through collaborative research agreements which include support for regulatory review, field testing, and legal/contractual agreements for protection of intellectual property rights (IPR). Efforts to determine the research priorities, innovative modalities for collaborative agreements, and value decisions on which these are based are reviewed as an example of ongoing international biotechnology initiatives.